Mimicking primary processes in photosynthesis-covalently linked porphyrin quinones - Speck, Marcus; Kurreck, Harry; Aguirre, Santiago; Dieks, Henrik; Gätschmann, Jörg; von Gersdorff, Jörg; Newman, Hans; Schubert, Heike; Stabingis, Thomas; Sobek, Jens; Tian, Peizhu; Wiehe, Arno (Radiation Physics and Chemistry, 1995)
Porphyrin quinones (P-Qs), covalently linked via different aliphatic bridges, have been synthesized and studies in their (porphyrin) cationic and (semiquinone) anionic radical states by EPR, ENDOR and TRIPLE resonance techniques. Electron transfer (ET) from the porphyrin donor to the quinone acceptor could be observed by time-resolved picosecond fluorescence spectroscopy (singlet ET) and by time-resolved EPR spectroscopy (triplet ET) in isotropic fluid solution and in anisotropic media (liquid crystals and reversed micelles). Steady-state in situ photoexcitation of P-Qs in CTAB cationic reversed micelles yielded the corresponding semiquinone radical anions. In TRITON X-100 reversed micelles both the radical cation of the porphyrin and the radical anion of the semiquinone could be detected, which occured in complete emission. In covalently linked porphyrin flavins ET from the photoexcited porphyrin fragment to the flavin and, in addition, energy transfer from the photoexcited flavin to the porphyrin could be observed. © 1995.